Not Quite The Taliban - Hindash, Fadi (Belgium : Epeios Productions, 2009)
The story of one man's frustration with his generation of young Arabs who appear to have succumbed to western ideologies and have attended the best western schools, yet prove to be more conservative than traditional Arabs when it comes to accepting or even addressing taboos like homosexuality. The half-Palestinian half-Lebanese director, who grew up in Dubai, puts himself on the line by speaking out about the hypocrisy of the society that prefers to ignore him and defines homosexuals as "eccentrics" with temporary deviances. This film is a confession and an angry outcry at the same time, trying to decipher a society trapped half-way between tradition and modernity.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films